2011
DOI: 10.1016/j.phpro.2011.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Accurate modeling approach for the structural comparison between monolayer polymer tubes and single-walled nanotubes

Abstract: In a recent computational study, we found highly structured ground states for coarse-grained polymers adsorbed to ultrathin nanowires in a certain model parameter region. Those tubelike configurations show, even at a first glance, exciting morphological similarities to known atomistic nanotubes such as single-walled carbon nanotubes. In order to explain those similarities in a systematic way, we performed additional detailed and extensive simulations of coarse-grained polymer models with various parameter sett… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…In the adf we clearly see the signals from two different regions with different chiralities as well as from defects in that structure. A detailed, systematic analysis of monolayer structures at high string attraction strength and different effective string thicknesses is subject of ongoing studies [20,21].…”
Section: Resultsmentioning
confidence: 99%
“…In the adf we clearly see the signals from two different regions with different chiralities as well as from defects in that structure. A detailed, systematic analysis of monolayer structures at high string attraction strength and different effective string thicknesses is subject of ongoing studies [20,21].…”
Section: Resultsmentioning
confidence: 99%
“…Sânchez-Portal et al 27 also found some dependence on nanotube radius in an ab initio study. A recent study 28 provides accurate parameters for all types of nanotubes and shows that the simple expression 8 for the radius as a function of n and m is more complex, 29 thereby further emphasizing the need to use atomistic models. We are unaware of a comphrehensive study that considers the effect of structure on multiple lateral modes of doubly clamped SWCNTs, and in view of the above-described contradictions, this issue requires clarification.…”
Section: Proposes That Chirality May Be Relevant In Calculations Of Ymentioning
confidence: 99%
“…5 in Ref. [36]). In Table 2, results for (6,0) and (4,3) tubes are therefore listed in the same row.…”
Section: Reproducing Swcnt Sequences Of Chiralitymentioning
confidence: 91%
“…(3.3) for the calculation of the SWCNT radius. This error can be bigger than the differences between radii of two SWCNTs of different type [36].…”
Section: Mapping Between Carbon Nanotubes and Polymer Tubesmentioning
confidence: 95%
See 1 more Smart Citation